Wielowymiarowa analiza efektywnosci instytucjonalnej w krajach Europy Srodkowo-Wschodniej w relacji do standardow OECD - Adam P. Balcerzak (Institute of Economic Research (IER), 2014)
– The article is devoted to measuring the effectiveness of institutional systems of developed countries in terms of their relevance to the requirements of the global knowledge-based economy. The aim of the article is to evaluate the results obtained by Visegrád Group in relations to OECD countries. In the first part of the article the most important factors determining the ability of a country to use the development potential of the knowledge-based economy was discussed. This analysis was based on the principals of institutional economics. Then taxonomic examination for OECD countries covering the period 1995-2010 was made. The empirical analysis utilized linear ordering, a procedure based on the Hellwig's method of pattern development. Data form Fraser Institute base created for Economic Freedom of the World Raptor was used.
Keywords: 330; institutional system; multivariate analysis; global knowledge-based economy